Demand on Delinquency and the Practice of Control for Traffic Laws Enforcement - Лейсан Ильгизаровна Халиуллина (Journal of Economic Sociology, 2010)
The object of the investigation is the inspectors for the road patrol service. The subject of the research is the system of the formal and informal penalties for the breaking of the traffic laws and control mechanisms. According to the data the usage of penalties is determined by two main factors. They are the economic motivation of the road patrol inspector (who is an active economic actor looking for the maximization of his utility and minimization of costs) and the restrictions that a road patrol inspector has according to the system. The organization (system) is considered to be a principal and an inspector is an agent. So that an inspector is considered to be an egoistic economic agent and at the same time as an agent whose activity depends on structural restrictions of the organization he works at. The costs of control and demand for delinquency are under analysis here.